2017
DOI: 10.1016/j.physbeh.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Lactose malabsorption and taste aversion learning

Abstract: Consumption of foods can be suppressed by two feeding system defense mechanisms: conditioned taste aversion (CTA) or taste avoidance learning (TAL). There is a debate in the literature about which form of intake suppression is caused by various aversive stimuli. For instance, illness-inducing stimuli like lithium chloride are the gold standard for producing CTA and external (or peripheral) painful stimuli, such as footshock, are the traditional model of TAL. The distinction between CTA and TAL, which have iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Yet, even the Lactose rats that continued to consume some amount of saccharin on the last trial in Experiment 2 also had smaller initial lick rates and burst sizes than their NaCl counterparts. A recent study by Arthurs et al [27] also found that pairing 0.1% saccharin with, in their case, a higher dose of lactose via intragastric infusion reduced initial lick rate and burst size. Although these altered lick patterns were not directly compared to those associated with LiCl in that study, the authors concluded that the change in these two aspects of licking indicate that Lactose conditioned an aversion to the taste CS.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Yet, even the Lactose rats that continued to consume some amount of saccharin on the last trial in Experiment 2 also had smaller initial lick rates and burst sizes than their NaCl counterparts. A recent study by Arthurs et al [27] also found that pairing 0.1% saccharin with, in their case, a higher dose of lactose via intragastric infusion reduced initial lick rate and burst size. Although these altered lick patterns were not directly compared to those associated with LiCl in that study, the authors concluded that the change in these two aspects of licking indicate that Lactose conditioned an aversion to the taste CS.…”
Section: Discussionmentioning
confidence: 90%
“…The literature is now replete with examples of various types of interoceptive stimuli that effectively condition reductions in intake of the associated taste CS. This includes, in addition to the ones already mentioned, motion/vestibular disturbance, GI pain, bacterial infection, chemotherapeutic drugs, and certain drugs of abuse, among others [e.g., [8, 15, 27–33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burst size data, which show that this measure is either unmodified or increased (10 mg/kg imipramine, first part of the experiment), do not lend support to the possibility that the reduced ingestion might be due to a drug-induced state of malaise, which is characterised by a reduction of this measure (e.g. [ 31 , 44 ]).…”
Section: Discussionmentioning
confidence: 91%